A construção da subjetividade em Macabéa : uma leitura de A Hora da estrela, de Clarice Lispector - Ferreira, Lívia Santos (2020)
The objective of this work is to analyze how the construction of subjectivity takes place in the character Macabéa, from the novel A hora da estrela, by Clarice Lispector, published in 1977. This analysis starts from the author's critical reception, using authors such as Nádia Battella Gotlib, Benjamin Moser, Youdith Rosenbaum, among others, in addition to the concept of subjectivity, which occurs through observations in the philosophical and literary fields. We bring the origin of the concept of subjectivity, starting from the pre-Socratic philosophers, also entering into the subjectivity subject in Romanticism and in striking aspects of the moderncontemporary novel. The novel, on which we dwell, which starts from the narrative about the northeastern Macabéa, at first is marked by the flow of consciousness, a characteristic of Clarician writings. In addition to the flow of consciousness and the search for the understanding of human existence, brought by the narrator Rodrigo S.M., ontology and the incompleteness of human experience are hallmarks of Clarice's literature, upon which elements of subjectivity are raised. We analyze the characteristics of the writer and her texts, metalanguage, epiphany, inner experience, until we reach Macabéa's subjectivity, crossing her trajectory with the search for the narrator Rodrigo S.M. for understanding herself. We take as theoretical contributions considerations of Márcia Lígia Guidin (2002), Anatol Rosenfeld (1985), Jena Laura da Cunha Santos (2000), among others.